2005
DOI: 10.1002/ejoc.200500369
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Fullerene Bromides and Chlorides

Abstract: Halogenated fullerenes have been subjects of intensive investigations since the discovery of fullerene, because of their possible further derivatization. This paper reviews the synthesis and molecular structures of fullerene bromides and chlorides, covering earlier work in this field and progress in synthetic methods developed by the authors. The use of inorganic chlorides and oxychlorides for the chlorination of fullerenes allowed the preparation of new compounds that have been fully characterized by single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…For example, theoretical calculations for non‐IPR C 60 Cl 8 predict it to be 1.4 eV lower in energy than the most stable octachloride of I h ‐C 60 8. Nevertheless, chlorination of C 60 with SbCl 5 under the similar conditions as reported is known to yield only IPR C 60 Cl 24 and C 60 Cl 30 molecules 15. Chlorination of C 70 ,16 C 78 ,17 and C 90 18 also leaves the σ networks of their carbon cages intact; the same applies to a different technique of chlorination of C 76 14 and C 80 19 at lower temperatures.…”
Section: Methodsmentioning
confidence: 78%
“…For example, theoretical calculations for non‐IPR C 60 Cl 8 predict it to be 1.4 eV lower in energy than the most stable octachloride of I h ‐C 60 8. Nevertheless, chlorination of C 60 with SbCl 5 under the similar conditions as reported is known to yield only IPR C 60 Cl 24 and C 60 Cl 30 molecules 15. Chlorination of C 70 ,16 C 78 ,17 and C 90 18 also leaves the σ networks of their carbon cages intact; the same applies to a different technique of chlorination of C 76 14 and C 80 19 at lower temperatures.…”
Section: Methodsmentioning
confidence: 78%
“…For more detailed information, see also the review by Troyanov and Kemnitz. [47] For C 76 Cl 18 , X-ray analysis demonstrated that the sp 2 -hybridized carbon atoms form a rather extended "aromatic girdle," which consists of 14 sixmembered cycles that form a helix in the same direction as the chlorine atoms. For C 80 Cl 12 , X-ray analysis demonstrated that the addition pattern of chlorine atoms has a notable feature, namely, the most pyramidal carbon atoms are not attacked during chlorination, although in other cases they have been found to be the most reactive ones.…”
Section: Electronic Rulesmentioning
confidence: 99%
“…Recently, many fullerene derivatives have been synthesized and characterized, such as C 76 Cl 18 ,41 C 80 Cl 12 ,42 C 60 Cl 30 ,43 and C 60 Cl 24 ,44 C 70 Cl 28 ,45 and C 76 Cl 34 46 by the use of this chemical‐synthesis method. For more detailed information, see also the review by Troyanov and Kemnitz 47. For C 76 Cl 18 , X‐ray analysis demonstrated that the sp 2 ‐hybridized carbon atoms form a rather extended “aromatic girdle,” which consists of 14 six‐membered cycles that form a helix in the same direction as the chlorine atoms.…”
Section: Fullerene Derivativesmentioning
confidence: 99%
“…Higher chlorides can be produced by using stronger chlorinating agents such as Cl 2 or some inorganic chlorides (ICl, SbCl 5 etc.) at higher temperature 16. For instance, recently chlorination of the mixture of higher fullerenes with SbCl 5 resulted in isolation and structural characterization of C 90 Cl 32 17.…”
Section: Introductionmentioning
confidence: 99%